Epidemiological Situation on Tularemia in the far Eastern Federal District (2000-2017) - T. N. Demidova; V. P Popov; T. V. Mikhailova; A. S. Cemichin; Y. S. Podobedova (Эпидемиология и вакцинопрофилактика, 2019)
Relevance Tularemia - natural focal zoonotic infection occupies an important place in the structure of human infectious pathology. The incidence is associated with natural foci, where there are favorable conditions for the existence of the pathogen, its circulation among rodents and other mammals. Natural foci of tularemia are widespread and are characterized by high environmental plasticity of the pathogen, which has polyhostality, polyvector, a plurality of transmission mechanisms, the duration of preservation of the pathogen in the external environment, especially at low temperatures, as well as the hydrophilicity of the pathogen and the ability to experience adverse conditions in a resting (uncultivated) form. Tularemia is a particularly dangerous infection, is included in the second group of pathogenicity.Aims. The purpose of this work is to identify the main patterns of functioning and epidemic manifestations of natural foci of tularemia in the far Eastern Federal district (far Eastern Federal district) on the basis of long-term monitoring and using various research methods.Results, The analysis of the epizootic state and epidemic manifestation of natural foci of tularemia in the territory of the far Eastern Federal district for 2000-2017 shows that the main regularities of the epidemic process remain in the natural foci of this infection. Given the nature of the epidemic manifestations of tularemia, due to different ways of infection, seasonality, vaccination, etc., it is necessary to improve the system of epidemiological surveillance of the state of natural foci of infection and develop a differentiated approach to the prevention of tularemia. The analysis revealed the dynamics of epizootic activity of natural foci of tularemia, confirmed by the release of cultures of the pathogen and positive serological findings of antibodies and antigen, and in recent years, DNA Francisella tularensis in biological objects. For the first time, a retrospective diagnosis of 249 serum tularemia of people living in the regions of the Kamchatka region and the Koryak Autonomous district was made, which made it possible to identify among the local population those who had been ill with tularemia at different times, which indicates the presence of natural foci of this infection. In the Khabarovsk territory and the Amur region, mixed infection of patients with two natural focal infections was revealed: tularemia - hemorrhagic fever with renal syndrome, tularemia - tick rickettsiosis. Thus, there is a possibility of simultaneous or consecutive infection of people with two, and possibly more natural focal infections in combined foci. Eleven years of observation of natural foci of tundra tularemia not subjected to anthropogenic and man-made impact on the island of Wrangel allowed to establish their epizootic activity, which is an epidemic danger for contingents traveling to temporary work in the areas of the island.Conclusions Analysis of the epidemic manifestations of natural foci of tularemia on the territory of the far Eastern Federal district in recent years has shown that immunization of the population living in enzootic areas for this infection is not carried out in full, and in some subjects is completely absent. Reducing the incidence of tularemia as a result of vaccination does not mean the recovery of natural foci, the potential danger of which continues to persist.